Pediatric Early Warning Score in Predicting Length of Stay in Hospital - Syed Bilal Hussain Shah, Hibba Kokab, Muhammad Rafay Jeelani (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: “To determine the predictive accuracy of pediatric early warning score to predict the length of hospital stay in children” Study Design: Cross sectional study Study place and duration: Department of Pediatrics, The Children’s Hospital, Lahore from June 2022 to August 2022. Methodology: After meeting inclusion and exclusion criteria 190 children were enrolled. Then child was examined for PEWS and score was noted. Then children were labeled as positive or negative for prolonged hospital stay (as operational definition). Children were managed as per standard protocol. All the children were followed-up in wards or intensive care unit till discharge and total hospital stay was noted. Results: The mean age of the children was 7.89±4.49 years, 103(54.21%) children were male. The sensitivity, specificity, PPV, NPV and diagnostic accuracy of PEW score of the children was 88.03%, 80.82%, 88.03%, 80.82% & 85.26% children respectively taking actual prolonged hospital stay as gold standard. Conclusion: From the findings of this study we may conclude that pediatric early warning score is a useful and reliable tool to predict the length of hospital stay in children. Keywords: Length of Hospital Stay, Pediatric Early Warning Score,